Can a Labour Market Assessment be used to Help Adolescent Girls and Young Women Improve their Employment Prospects in South Africa? - Mvunabandi, Jean Damascene; Nomala, Bomi; Marimuthu, Ferina (International Review of Management and Marketing, 2023)
This article investigated how labour market assessment intervention through employability training can be used as a catalyst to improve employment pathways among adolescent girls and young women (AGYWs) in South Africa. This study adopted quantitative and descriptive research approaches via longitudinal data collection. Secondary data was collected from 3584 AGYWs using a questionnaire survey during employability training from July-October 2021. Robustness analysis was performed using descriptive statistics using SPSS version 27.0. The empirical findings proved that employability training significantly improved the capabilities of adolescent girls and young women on labour market assessments. Relying on these empirical findings, this study proposes a framework for linking AGYWs and the labour market through an employability training capability-based conceptualised model. This study contributes to the current body of knowledge and further contributes to the career development and employability among adolescent girls and young women required to cope with the labour markets in South Africa.